2000
DOI: 10.1111/j.1574-6968.2000.tb09056.x
|View full text |Cite
|
Sign up to set email alerts
|

The polyester polyurethanase gene (pueA) fromPseudomonas chlororaphisencodes a lipase

Abstract: A gene (pueA, polyurethane esterase A) encoding an extracellular polyurethanase (PueA) was cloned from Pseudomonas chlororaphis into Escherichia coli. The enzyme secreted from E. coli showed esterase activity when assayed with p-nitrophenyl acetate. Subcloning of a 3. 2-kb SalI-EcoRI fragment into a T7 RNA polymerase expression vector (pT7-6) produced a (35)S-labeled protein of 65 kDa. Nucleotide sequencing of pueA showed an open reading frame encoding a 65-kDa protein of 617 amino acid residues, with the seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Many secreted enzymes from fungal and bacterial organisms also possess the ability to degrade PUs of various formulations (4,6,7,(35)(36)(37)(38). Genes that encode enzymes capable of degrading PU ex vivo from some of these organisms have also been identified and cloned (5,9,11). Comparison of these gene sequences revealed that the gene products from these diverse organisms all contain a lipase domain and are predicted to be secreted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many secreted enzymes from fungal and bacterial organisms also possess the ability to degrade PUs of various formulations (4,6,7,(35)(36)(37)(38). Genes that encode enzymes capable of degrading PU ex vivo from some of these organisms have also been identified and cloned (5,9,11). Comparison of these gene sequences revealed that the gene products from these diverse organisms all contain a lipase domain and are predicted to be secreted.…”
Section: Discussionmentioning
confidence: 99%
“…Several Pseudomonas species including Pseudomonas chlororaphis, Pseudomonas aeruginosa, and Pseudomonas fluorescens have been shown to degrade a model polyester PU, Impranil DLN (Impranil) (4)(5)(6). Three PU-degrading enzymes have been purified and characterized from some of these strains, including polyurethane esterases A (PueA) and B (PueB) from Pseudomonas chlororaphis (5,9) and polyurethane lipase (PulA) from P. fluorescens (5,(9)(10)(11). Although they are often referred to as "polyurethanases," these enzymes are more accurately classified as extracellular lipases and esterases.…”
mentioning
confidence: 99%
“…All the purified serine hydrolases above have the same hydrolytic capacity to emulsify polyester PUR. In addition, they also cloned a gene named pulA from Pseudomonas fluorescens and two genes, pueA and pueB, from Pseudomonas chlororaphis (Stern and Howard, 2000;Howard et al, 2001b). These genes encoded three different esterases involved in the microbial degradation of emulsified polyester PUR by Pseudomonas fluorescens and Pseudomonas chlororaphis.…”
Section: Purmentioning
confidence: 99%
“…strains MIS38 and KB700A (Amada et al , 2000; Rashid et al , 2001;). The polyester polyurethanases PueA and PueB of Pseudomonas chlororaphis are also classified as lipases (Stern & Howard, 2000). …”
Section: Classes Of Rtx Proteinsmentioning
confidence: 99%